AN ANALYSIS OF STUDENTS’ MOTIVATION USING SNAPCHAT IN LEARNING READING - Meysi Salsadila; Sugianto (Journal of English Education and Literature, 2026)
This study examined how Snapchat influences students’ motivation toward reading English. A mixed methods approach was used by combining questionnaire data and interview data from five participants. Quantitative data were evaluated descriptively, whilst qualitative data were analyzed thematically. Data were collected through semi-structured interviews and questionnaire, employing various platforms such as Google form and direct calls among university students. The analysis centered on intrinsic and extrinsic motivations as informed by the Self-Determination Theory, focusing on the dimensions of autonomy, competence, and relatedness. Findings indicate that Snapchat’s interactive and visual elements notably bolster students’ intrinsic motivation by fulfilling their needs for autonomy, competence, and social connections, while extrinsic motivation factors were less influential. The study concludes that Snapchat presents a promising avenue for enhancing engagement and motivation in English reading among university learners.